CD200–CD200R immune checkpoint engagement regulates ILC2 effector function and ameliorates lung inflammation in asthma - Pedram Shafiei-Jahani (Nature Portfolio, 2021)
The role of the CD200–CD200R axis in regulating pulmonary inflammation is not completely understood. Here the authors show CD200R is expressed on type 2 innate lymphoid cells (ILC2s), and its engagement by CD200 ameliorates airway hyperreactivity and allergic asthma via inhibition of NF-κB signaling.